A New Dynamic Simulation Test Method of Intelligent Electricity Metering System. Issue 1 (May 2021) - Xue, Yang; Song, Runan; Yang, Yining; Wang, Cong; Yang, Liu
Abstract: Electricity metering is the core supporting technology for realizing accurate perception of electricity consumption, reasonable dispatching of power grids, rapid market response, diversified charging and new forms of electricity marketing. However, due to the significant differences in the actual metering environment, the operation of the electricity metering and information collection system is unstable, showing many problems such as unsuccessful parameter delivery and low acquisition success rate, which severely restricts the development of smart grid two-way interactive technology and the realization of smart electricity consumption in the last mile. There is an urgent need for a reliable and accurate dynamic simulation and systematic testing method to realize the reproduction and testing of various field faults. In this paper, we propose a new type of dynamic simulation test method for intelligent electricity metering system, which can realize the performance test, fault dynamic simulation, location and recovery of each functional unit of the master station, collection terminal and smart meter. Through experimental testing, our dynamic simulation test methods can realize the rapid recurrence of on-site problems, improve the high reliability and normal operation of the electric energy metering information collection system.